2022
DOI: 10.3390/molecules27154782
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Control Using Far-Infrared Irradiation for Producing Deglycosylated Bioactive Compounds from Korean Ginseng Leaves

Abstract: Although ginseng leaf is a good source of health-beneficial phytochemicals, such as polyphenols and ginsenosides, few studies have focused on the variation in compounds and bioactivities during leaf thermal processing. The efficiency of far-infrared irradiation (FIR) between 160 °C and 200 °C on the deglycosylation of bioactive compounds in ginseng leaves was analyzed. FIR treatment significantly increased the total polyphenol content (TPC) and kaempferol production from panasenoside conversion. The highest co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The polyphenols are important antioxidant contributors [ 10 , 11 , 12 , 13 ] and the significantly increased total phenolic content in the thermally treated M. charantia can support the increased antioxidant activities, which were evaluated using three different assays ( Figure 2 and Figure 3 ). A chromatogram at 280 nm is widely used to study the polyphenols because the absorption at this wavelength is suitable for detecting a large number of such compounds [ 32 ]. Based on the lambda max of the peaks at 280 nm in our data and the phenolic acid profiling of M. charantia from a previous report [ 24 ], the peaks we detected are considered to be phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenols are important antioxidant contributors [ 10 , 11 , 12 , 13 ] and the significantly increased total phenolic content in the thermally treated M. charantia can support the increased antioxidant activities, which were evaluated using three different assays ( Figure 2 and Figure 3 ). A chromatogram at 280 nm is widely used to study the polyphenols because the absorption at this wavelength is suitable for detecting a large number of such compounds [ 32 ]. Based on the lambda max of the peaks at 280 nm in our data and the phenolic acid profiling of M. charantia from a previous report [ 24 ], the peaks we detected are considered to be phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to acknowledge that FIR drying also has its drawbacks, including the generation of high heat, which can potentially lead to burns upon exposure [18]. In our previous research, we showed that FIR can significantly increase the TPC in ginseng leaves and promote ginsenoside transformations [12]. Geng et al [19] found in their research that after infrared drying, the content of TPC in carrot slices increased, and the antioxidant activity also increased significantly.…”
Section: Introductionmentioning
confidence: 87%
“…The deglycosylation of panasenoside is concurrent with kaempferol degradation; increasing the FIR temperature gradually caused the panasenoside deglycosylation rate to become lower than the kaempferol degradation rate. This explains why the panasenoside content in American ginseng leaves decreased rapidly while the kaempferol content increased relatively slowly, reaching the highest value after FIR treatment at 190 • C [12]. Although the kaempferol content in American ginseng leaves reached the highest value after FIR treatment at 190 • C, its content in ginseng leaves was different, and it stopped increasing after FIR treatment at 180 • C. This could have been caused by the different compositions and amounts of panasenoside in the raw material used.…”
Section: The Effect Of Fir Heat Treatment On the Amounts Of Panasenos...mentioning
confidence: 98%
See 1 more Smart Citation
“…Both the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging ability and the 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging ability were used to assess the antioxidant activities of the samples. These assays were performed as described by Lim et al [ 26 ] and Duan et al [ 27 ], respectively. The radical scavenging activity of the samples was expressed as mg of vitamin C equivalent (VCE)/g dry weight.…”
Section: Methodsmentioning
confidence: 99%